Analisis Transparansi Dan Akuntabilitas Dana Kelurahan : (Studi Kasus Kantor Lurah Karang Berombak, Kecamatan Medan Barat, Kota Medan) - Rina Halizah Nasution; Nurbaiti Nurbaiti; Laylan Syafina (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research is useful for ensuring transparency and accountability The use of sub-district funds at the Karang Berombak Village Head Office is distributed randomly broad and easily accessibleble to the public, especially the information presented in The format is simple to understand and listed in detail. As well as for increasing community empowerment in terms of utilizing these funds. This research uses a qualitative descriptive approach. Technique Data collection used in this research was interviews and documentation. The subjects of this research were a total 5 people who were devices sub-districts at the Karang Berombak Village Head Office, namely Village Head, Secretary, Treasurer, Head of Development, and Head of Environment XIII. The research results explain that Transparency and Accountability of Village Funds at the Lurah Office Karang Berombak, West Medan District, Medan City is transparent and accountability can be seen from a participatory process that involves all levels community by gathering and approving community aspirations although budget management is not made public, transparency and accountability is maintained through active community involvement and positive responses village head towards criticism and suggestions given by the community and them has supervised the use of sub-district funds. In this way, sub-district funds can be used appropriately to meet needs community needs and create a better and empowered environment.